گواستنەوە لە بەندەکانی ڕێکەوتنامەی سایکس - پیکۆ دا لێکۆڵینەوەیەک لە جوگرافیای گواستنەوە دا - كریم, احمد رفیق; محمد, شاد حه‌مید (Sulaimani Journal for Humanities, 2018)
Transportation in the Sykes-picots articles agreement Kurdistan geographical location and economy cased to disputed area between the grate international states and regional states, all of them direct and indirect want to control Kurdistan, so that France and Britain divided inheriting ottoman empire (include Kurdistan) between themselves in 1916, in the Sykes –picot agreement contains transportation terms .as we know they through in Kurdistan, there for we have chosen the transportation in the agreement to make geographical analyses.